Suppression of inner surface roughening during hollow sinking of SUS304 stainless-steel tubes with {111} fiber texture - Takuma Kishimoto; Koki Norizuki; Hisashi Sato (Journal of Materials Research and Technology)
The surface roughness and Taylor factor of the inner surfaces of the stainless-steel microtubes were evaluated to clarify the mechanism behind the suppression of inner surface roughening during hollow sinking. SUS304 microtubes with an outer diameter of 2.0 mm and a wall thickness of 0.09 mm were drawn without an inner tool. The inner surface roughnesses and crystal orientations of the original and drawn tubes were evaluated. The results indicated that the Taylor factors of the {112}<111> and {110}<111> textures were larger and smaller, respectively, than those of the other textures in the {111} fiber texture during wall-thickening. Therefore, inhomogeneous deformation was more likely to occur during wall-thickening because the Taylor factor was distributed over a wide range. By contrast, all grains in the {111} fiber texture had nearly the same Taylor factor during wall-thinning. Consequently, differences in the Taylor factor among the grains of the {111} fiber texture were smaller during wall-thinning than during wall-thickening. These results indicate that inhomogeneous deformation of the grains was less likely to occur during wall-thinning than during wall-thickening. Consequently, the coefficient of roughening evolution considering the effect of changes in surface area decreased by up to 60% owing to wall-thinning during hollow sinking.